1993
DOI: 10.1159/000100637
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy in Frame-Based and Frameless Stereotaxy

Abstract: Stereotactic surgery is currently undergoing great changes with a large number of frameless methodologies being developed alongside traditional frame-based systems. As a result, there is considerable uncertainty over the future clinical roles of the numerous stereotactic options now offered. We have reviewed the current scientific issues regarding accuracy in both frame-based and frameless stereotaxy. Frame-based systems have the advantage of proven clinical utility and instrument carriage with a high degree o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

1997
1997
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(22 citation statements)
references
References 11 publications
0
20
0
Order By: Relevance
“…However, all of the published clinical accuracy studies and the majority of the laboratory studies to date have used adhesive 'doughnut' markers or anatomical fiducials [4][5][6][8][9][10][11][12][13][14]. There are several factors which contribute to inaccuracy when using this type of fiducial marker, in- In the first three cases, only localization error was measured.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, all of the published clinical accuracy studies and the majority of the laboratory studies to date have used adhesive 'doughnut' markers or anatomical fiducials [4][5][6][8][9][10][11][12][13][14]. There are several factors which contribute to inaccuracy when using this type of fiducial marker, in- In the first three cases, only localization error was measured.…”
Section: Discussionmentioning
confidence: 99%
“…This is the minimum number of points for paired-point registration, there is no redundancy, and the points are all coplanar, making the registration solution suboptimal. It has been shown that distributing fiducials throughout the volume of interest increases registration accuracy [14]. Registration is the 'Achilles' heel' of image-guided surgery, so misregistration can have the largest adverse effect.…”
Section: Hendersonmentioning
confidence: 99%
“…The positions of these points are then correlated with the corresponding surface from image data, and an estimate of the residual error is given 194 . This method is time consuming 83 . Methods to speed up data collection include pointers with automated surface-contact detection (Softouch, Brainlab, Heimstetten, Germany), a robot-guided registration tool 50 and continuous collection of surface points 69,79 .…”
Section: Surface Registrationmentioning
confidence: 99%
“…The development of techniques for neuronavigation rendered it possible to perform stereotactic brain surgery without a conventional frame fixed to the skull bone (frameless stereotaxy) [6,7] .…”
Section: Introductionmentioning
confidence: 99%